(1) In a convergent geometric series, the sum of the first four terms is \( \frac{80}{3} \) and the sum to infinity of the series is 27. Determine the general term.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve this problem, we start by recalling the formulas for the sum of a geometric series. The sum to infinity \( S \) for a convergent geometric series is given by \[ S = \frac{a}{1 - r} \] where \( a \) is the first term and \( r \) is the common ratio (with \( |r| < 1 \)). Here, we know: \[ S = 27 \implies \frac{a}{1 - r} = 27 \tag{1} \] Next, the sum of the first \( n \) terms of a geometric series is given by \[ S_n = a \frac{1 - r^n}{1 - r} \] We want the sum of the first four terms, \( S_4 \): \[ S_4 = a \frac{1 - r^4}{1 - r} = \frac{80}{3} \tag{2} \] Now we have two equations to work with: equation (1) for the sum to infinity and equation (2) for the sum of the first four terms. We can isolate \( a \) from (1): \[ a = 27(1 - r) \tag{3} \] Substituting (3) into (2): \[ 27(1 - r) \frac{1 - r^4}{1 - r} = \frac{80}{3} \] This simplifies to: \[ 27(1 - r^4) = \frac{80}{3} \] Now, multiply both sides by 3 to eliminate the fraction: \[ 81(1 - r^4) = 80 \] Then, divide by 81: \[ 1 - r^4 = \frac{80}{81} \] Thus, \[ r^4 = 1 - \frac{80}{81} = \frac{1}{81} \] Taking the fourth root gives us: \[ r = \frac{1}{3} \] Next, we substitute \( r \) back into equation (3) to find \( a \): \[ a = 27(1 - \frac{1}{3}) = 27 \times \frac{2}{3} = 18 \] Now we have \( a = 18 \) and \( r = \frac{1}{3} \). The general term of a geometric series is given by: \[ T_n = a \cdot r^{n-1} \] Substituting \( a \) and \( r \): \[ T_n = 18 \left(\frac{1}{3}\right)^{n-1} \] Thus, the general term of the given convergent geometric series is: \[ \boxed{18 \left(\frac{1}{3}\right)^{n-1}} \]